New research of hilltop settlements on the eastern fringes of Pohorje and the northern Slovenske gorice (NE Slovenia) - Črešnar, Matija; Vinazza, Manca (Arheološki vestnik, 2019)
This contribution presents the results of multidisciplinary investigations of the wider areas of the Poštela near Maribor and Novine/Bubenberg (or Hoarachkogel) near Šentilj archaeological sites. Both of them include a fortified settlement, cemeteries with flat graves and barrows, and sunken paths, which shed light on our understanding of the integration of the sites with their environment. During the Early Iron Age, Poštela and Novine/Bubenberg were two of the major regional centres between the Alps and the Pannonian Plain. Other settlements, probably of lower status, were discovered in their vicinity. Two of them are Čreta near Slivnica and Plački vrh/Platsch, and they are included in this study. This contribution does not summarize all the findings, since some investigations are still in progress. Nevertheless, it presents some innovations that complement our knowledge of certain segments of the Early Iron Age in the northeastern Slovenia and in a wider cultural circle. Our understanding of hillforts is aided by the new findings about the earthworks that transformed the interior of the settlements. It is presented how we can investigate barrow cemeteries and even their expansion with modern approaches, without having to resort to excavations. Two new flat cemeteries have been discovered, in addition to a form of burial previously unknown in cemeteries around hillforts – a grave, surrounded by a ditch and without a barrow.